Efficiency of domestic wastewater solar disinfection in recatos with different colors - Queluz, João Gabriel [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP] (My University, 2014)
The aim of this study was to evaluate the efficiency of domestic wastewater solar disinfection for agriculture reuse in solar reactors with different colors: black, white and raw concrete. After passing through a septic tank, the wastewater was conducted to the reactors until the water depth reaches 10 cm and it was exposed to sunlight for three consecutive days. The disinfection efficiency was evaluated by the concentration of E. coli, chemical oxygen demand, effluent temperature, global radiation, UV radiation, pH and total suspended solids and the data was analyzed by regression analysis. The results show that the effluent in different reactors had distinct temperatures: the highest rates were observed in the black reactor and the smallest in the white, however these differences were slight (on average 2 ºC) and the statistical analysis did not show a significant difference (p ≤ 0.05) between the efficiency in the reactors. The collected data allowed the development of a mathematical model that represents the remaining population of fecal coliforms in wastewater after being exposed to a certain dose of solar radiation. In conclusion, the reactor color does not alter the disinfection efficiency and the most important process variables are the UV-A radiation and total suspended solids concentrations
Keywords: Solar reactor; SODIS; Solar radiation; Fecal coliforms